Liberties of genome and medical pathogenetics - V. P. Puzyryov (Бюллетень сибирской медицины)
New phenomena in structural and functional organization of the human genome, which turned out to be unexpected for the postulates of classical genetics (liberties of genome) are presented. Modern ideas on forms of inherited variability are given. Participation of new genomic phenomena in pathogenetics and in revealing of new form of human pathology (prion diseases, mitochondrial diseases, trinucleotide repeats expansion, genomic imprinting) is noted. The significance of synthropy conception for the investigation of genetics of common diseases is substantiated. The thesis on the unity of three parts of medicine (social, genomic, and individualized) is put forward.